Novel Indications for Benzodiazepine Antagonist Flumazenil in GABA Mediated Pathological Conditions of the Central Nervous System - Hulse, Gary; Kelty, Erin; Hood, Sean; Norman, Amanda; Rita Basso, Maria; Stuart Reece, Albert (Current Pharmaceutical Design, 2015)
This review paper discusses the central role of gamma-aminobutyric acid (GABA) in diverse physiological systems and functions and the therapeutic potential of the benzodiazepine antagonist flumazenil (Ro 15- 1788) for a wide range of disorders of the central nervous system (CNS). Our group and others have studied the potential of flumazenil as a treatment for benzodiazepine dependence. A small but growing body of research has indicated that flumazenil may also have clinical application in CNS disorders such as Parkinson’s disease, idiopathic hypersomnia and amyotrophic lateral sclerosis. Despite this body of research the therapeutic potential of flumazenil remains poorly understood and largely unrealized. The purpose of this paper is not to provide an exhaustive review of all possible therapeutic applications for flumazenil but rather to stimulate research interest, and discussion of the exciting therapeutic potential of this drug for a range of chronic debilitating conditions.
Keywords: idiopathic hypersomnia